Keterlibatan Orang Tua dalam Pendidikan Al-Qur’an untuk Anak Usia Dini - Ambarwati, Rania; Sri Wulan; Elindra Yetti (Pendidikan Guru PAUD Universitas Persatuan Guru Republik Indonesia Semarang, 2025)
The Qur’an, as the primary guide for Muslims, needs to be introduced from an early age. Parental involvement is considered crucial in shaping children's moral and religious foundations, particularly in the teaching of the Qur’an to young children. This study aims to comprehensively review various literature concerning parental involvement in Qur’anic education for early childhood. Utilizing a literature review method, this article identifies and analyzes existing research and studies related to parental engagement in Qur’anic education. The selection process began with searches through Google Scholar, ultimately resulting in 15 relevant articles on parental involvement in Qur’anic education. The findings indicate that there is still a lack of resources addressing this topic. The review reveals that parental involvement takes various forms, ranging from direct guidance to hiring tutors. Additionally, factors such as parents' educational level, time commitment, and religious understanding influence the extent of their involvement. The study concludes that parental involvement in Qur’anic education for early childhood is vital for supporting children's moral and religious development. This article recommends strengthening the role of parents through more structured mentoring and training programs, as well as fostering more intensive collaboration between educational institutions and families.